Effect of Accelerated Aging on Color Change of Direct and Indirect Fiber-Reinforced Composite Restorations - Masomeh Hasani Tabatabaei; Farnaz Farahat; Elham Ahmadi; Zahra Hassani (Tehran University of Medical Sciences, 2016)
Objectives: The aim of this study was to assess the effect of artificial accelerated aging (AAA) on color change of direct and indirect fiber-reinforced composite (FRC) restorations. Materials and Methods: Direct (Z250) and indirect (Gradia) composite resins were reinforced with glass (GF) and polyethylene fibers (PF) based on the manufacturers' instructions. Forty samples were fabricated and divided into eight groups (n=5). Four groups served as experimental groups and the remaining four served as controls. Color change (∆E) and color parameters (∆L*, ∆a*, ∆b*) were read at baseline and after AAA based on the CIELAB system. Three-way ANOVA and Tukey's test were used for statistical analysis. Results: Significant differences were found in ΔE, ΔL*, Δa* and Δb* among the groups after AAA (P<0.05). Most of the studied samples demonstrated an increase in lightness and a red-yellow shift after AAA. Conclusions: The obtained ∆E values were unacceptable after AAA (∆E≥ 3.3). All indirect samples showed a green-blue shift with a reduction in lightness except for Gradia/PF+ NuliteF.